TUNTUTAN DWANGSOM DALAM SENGKETA PEMILIKAN TANAH (Studi Terhadap Permohonan Kasasi yang Dikabulkan pada Putusan Mahkamah Agung No. 1429K/Pdt/2006) - Sanyoto Sanyoto; Ziad Ziad; Antonius Sidik Maryono; Desy Perdani Yuris (Faculty of Law, Universitas Jenderal Soedirman, 2008)
Plaintiff that feels disadvantage because the rights impinged in the rule of procedure of civil law he or she can file a main claim by accompanied with addition claim. One of addition claim which can be asked plaintiff is to be sued punished to pray force money (dwangsom) every day to the negligence fulfilling justice decision. Rule of dwangsom there is in section 606 RV which in practice jurisdiction still applying where dwangsom is pressure tool which psychologically the side of sued to be defeated soon will fulfill main punishment in content of judge decision having the character of condemnatory which is not punishment of payment of money but in the form or real execution or realization as soon as possible. In decision of Mahkamah Agung No 1429 K/Pdt/2006 Plaintiff bringing a lawsuit to the court on the basis of property to land mastered by opponent is againts the law which the main claim is she or he expressed as valid owner to dispute object and express deed is sued has done deed to fight against law that is mastering disputed site without legal right and surrender claim of land with a width of 744 m2 any unconditional and force money (dwangswom) equal to 100.000, per day since decision obtains permanent legal force. Initially in first level of court (P.N. MALANG) Plaintiff claim is refused, then plaintiff submits effort of appeal law to P.T. Surabaya. On the basis of the matter is plaintiff applies cassation to Mahkamah Agung and granted because subordinate court has wrong applies law. Key word: dwangsom, final punishment, mahkamah agung